Hybrid placement technique for hepatic hilar obstruction using a new uncovered self-expandable metal stent - Ogura, Takeshi; Yamada, Masanori; Ueno, Saori; Fukunishi, Shinya; Higuchi, Kazuhide (Endoscopy International Open, 2019)
Background and study aim Recently, a novel technique combining stent-in-stent (SIS) and side-by-side (SBS) technique (hybrid technique) has been reported. This technique may have application for hepatic hilar obstruction (HBO) because it reduces the number of times the stent mesh has to be passed. However, to the best our knowledge, evaluation of its use in that setting has not been reported. Recently, a new uncovered self-expandable metal stent (UCSEMS) has become available in Japan. The diameter of this stent delivery shaft is only 5.4 Fr, and the discrepancy between the guidewire and top of stent delivery system is strongly reduced. We herein report technical tips for hybrid metal stent deployment for high-grade HBO using this novel UCSEMS. Hybrid metal stent deployment using he novel UCSEMS was attempted in seven patients. Technical success was obtained in all patients. Mean procedure time was 33.3 minutes (range, 27 to 43). Clinical success was obtained in six patients. Median stent patency was 109 days (range, 48 – 160 days).In conclusion, the hybrid metal stent placement technique appears to be useful using the new UCSEMS because of its fine-gauge stent delivery system.